Neutralization mechanisms in He+-Al surface collisions - Bajales Luna, Noelia (2007)
From a quantum mechanical calculation where the populations of He ground and first excited states are properly taken into account, we can identify for the first time the neutralization to the He first excited state as an operative mechanism in He+–Al surface collisions. This identification allows us to understand the presence of high energy electrons in the ion induced electron emission spectra, through the inclusion of Auger deexcitation as an electron emission source, as well as to suggest a possible cause for the disagreement still found between theory and experiments in low energy ion scattering (LEIS) for this system.